Fostering Self-Regulated Learning Through a School-Based Habituation Program in Vocational Education - Sakinah Mawaddah; Nur Jannah; Andi Bahtiar; Muhamad Apriyadi; Yenny Merinatul Hasanah (Journal of Educational Management Research, 2026)
This study aims to analyze the role of the SIBERTA (Siswa Berhati Imkata) Program as a school-based habituation program in fostering self-regulated learning and strengthening an ecosystem of student independence in vocational education. A qualitative case study design was employed using purposive sampling to select school leaders, advisory teachers, homeroom teachers, and students as participants. Data were collected through observations, semi-structured interviews, and document analysis, and their credibility was ensured through source and method triangulation. The findings indicate that the SIBERTA Program effectively promotes students’ self-regulated learning by strengthening six key dimensions aligned with the Pancasila Student Profile: responsibility, risk management, initiative, autonomous decision-making, self-reflection to reduce procrastination, and consistency in daily learning practices. These findings demonstrate that structured habituation integrated into school culture supports students in developing self-control, learning independence, and positive behavioral habits despite challenges posed by the digital era. The study implies that school-wide culture-based intervention programs can serve as an effective strategy for enhancing self-regulated learning and independent character development among vocational high school students.